Status ontologiczny wzorów biografii = The ontological status of biography models - Hajduk, Edward (1932-2015) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The author performs a review of the understanding of the concept of biography model in social science using the wide tradition of German and Anglo-Saxon sociology. He further shows the relationship between the model of a biography, the model of a person and the course of one`s life. There is a discussion on the functions fulfilled by biography models in the lives of living individuals.
Keywords: ontologia; biografia; model; wzór; nauki społeczne